The Role of the Church in Teaching Effective Parenting Methods to Protect the Alpha Generation from the Dangers of Gadget Addiction - Timothy Nathaniel Halim; Nicodemus Widiutomo; Rocky Nagoya; Tumpahan Manik (Jurnal Indonesia Sosial Sains, 2024)
This research explores the church's role in supporting parents of Generation Alpha and implementing effective parenting methods to prevent gadget addiction. This research collected and analyzed secondary data from relevant scientific journals, books, and news articles through a literature study approach. The results show that churches are important in providing education and resources for parents to face parenting challenges in the digital age. The research suggests that the integration of spiritual values and faith-based parenting guidelines can help parents in guiding their children to face the risks of device addiction. Furthermore, the study identified the need for educational programs specifically designed to equip parents with practical strategies in regulating their children's use of technology. The results of this study contribute to the understanding of the importance of synergy between church and family in educating children in the digital age.